Health Canada Usage of Real World Evidence (RWE) in Regulatory Decision Making compared with FDA/EMA usage based on publicly available information: Real-World Evidence used by Health Canada in Regulatory Decision Making - Lau, Catherine; Jamali, Fakhreddin; Loebenberg, Raimar (Journal of Pharmacy & Pharmaceutical Sciences, 2022)
Purpose: Between January 2020 and December 2021, Health Canada provided a Summary Basis of Decision (SBD) for each of 110 products approved, including 29 oncology products and 21 non-oncology orphan drugs. This review sought to gain insight into how Real Word Evidence (RWE) impacts regulatory decision making. Methods: SBDs for oncology drugs and non-oncology orphan drugs were reviewed for evidence of use of the RWE or historical data to support regulatory decisions. This information was compared with both FDA and EMA reviews. Results: For the 29 Health Canada-approved oncology products, 11 were approved with Notice of Compliance with Conditions (NOCc) status. Two NOCc approvals received extensive RWE reviews, while two other approvals briefly mentioned the use of RWE/historical data. Of the 12 NOC approvals, one received RWE reviews. FDA also approved all 29 drugs, 14 of which received extensive comments on RWE and/or historical data and 8 of which mentioned RWE or historical data. EMA approved 25 of the 29 products and provided extensive comments on 10. Four products received a mention of RWE review. The percentages of submissions with RWE/historical reviews conducted by Health Canada, FDA and EMA were 24.1, 75.9 and 56.0 respectively. Of the 21 non-oncology orphan drugs, Health Canada provided priority review status to 11, with extensive RWE comments in 5 and the mention of RWE in 2 of the regular approvals. Two approvals that used third-party data were not included in the comparison. FDA approved 19, and provided extensive RWE assessment on 5 and mentioned use of historical data in 8. EMA approved 17 and provided extensive RWE and historical comments in 7 and mentioned historical data in 4. The percentages of submissions with RWE/historical reviews by Health Canada, FDA and EMA were 36.8, 68.4 and 64.7 respectively. Conclusions: Use of Real World Data is common among FDA/EMA reviews and Health Canada used RWE in recent NOCc and orphan drug approvals.